(untitled) (The Pretoria Student Law Review, 2021)
This note analyses the United States Supreme Court’s decision in Stop the Beach Renourishment, Inc. v Florida Department of Environmental Protection. This note focuses on whether the Beach and Shore Preservation Act constitutes an unconstitutional taking of littoral owners’ right to accretions through authorisation of beach restoration projects. Part II of this note provides background information on littoral rights, the Beach and Shore Preservation Act, and the Court’s decision in Stop the Beach Renourishment, Inc. v Florida Department of Environmental Protection. Part III analyses the Court’s decision and concludes with a finding that the Beach and Shore Preservation Act constitutes an unconstitutional taking of littoral owners’ vested right to accretions. After a careful analysis of the three main cases relied on in the Court’s decision, the real background principles of Florida property law come to light; the state does not have a right to fill sovereign submerged lands adjacent to littoral property it does not own, and littoral property owners have a vested right to accretions. This vested right to accretions is found not only in common law but in the Florida Constitution and in Florida Statutes. By setting a fixed erosion control line as the boundary between private and sovereign lands, the Act unconstitutionally eliminates the littoral owners’ vested right to accretions without the occurrence of a justifying avulsive event. The purpose of this article is to stress that the Florida Supreme Court and the United States Supreme Court severely misinterpreted Florida property law. I am compelled, based on my conclusions regarding the underlying property law, to state that the Supreme Court should have resolved the judicial takings issue. My interest, however, is in water law and showing that two important courts made a fundamental mistake in categorising the underlying property law. Judicial takings are an issue in this case, but many other scholars have discussed it and I reserve the issue for another day.